Development of a sensitive immunochromatographic kit using fluorescent silica nanoparticles for rapid serodiagnosis of amebiasis. Issue 14 (9th May 2018) - Tachibana, Hiroshi; Kakino, Azumi; Kazama, Makoto; Feng, Meng; Asai, Satomi; Umezawa, Kazuo; Nozaki, Tsukasa; Makiuchi, Takashi; Kamada, Takayuki; Watanabe, Hideki; Horiki, Noriyuki; Cheng, Xunjia; et al.
Abstract: We have previously shown that the C-terminal region of the intermediate subunit of Entamoeba histolytica galactose- and N -acetyl-D-galactosamine-inhibitable lectin (C-Igl) is a useful antigen for serodiagnosis of amebiasis. An immunochromatographic kit was developed using fluorescent silica nanoparticles coated with C-Igl prepared in Escherichia coli . Samples for examination were added to the freeze-dried particles and then applied to the immunochromatographic device, in which a test line on the membrane was also coated with C-Igl. Fluorescent intensity was measured using a hand-held reader. In an evaluation of the kit using a human monoclonal antibody, the minimum amount of C-Igl specific antibody showing positive results was 100 pg. In the evaluation of serum samples with different antibody titers in indirect immunofluorescent antibody tests in the kit, 20 µ L of serum was sufficient to obtain positive results at 30 min. Serum samples from symptomatic patients with amebic colitis and amebic liver abscess and those from asymptomatic E. histolytica -cyst carriers showed positive results in the kit. Based on evaluation using sera from healthy controls and patients with other infectious diseases, the sensitivity and specificity of the kit were 100 and 97.6%, respectively. Therefore, we conclude that the newly developed kit is useful for rapid serodiagnosis of amebiasis.